Evaluation of Cytotoxicity and α-Glucosidase Inhibitory Activity of Amide and Polyamino-Derivatives of Lupane Triterpenoids - Oxana B. Kazakova (Molecules, 2020)
A series of two new and twenty earlier synthesized branched extra-amino-triterpenoids obtained by the direct coupling of betulinic/betulonic acids with polymethylenpolyamines, or by the cyanoethylation of lupane type alcohols, oximes, amines, and amides with the following reduction were evaluated for cytotoxicity toward the NCI-60 cancer cell line panel, α-glucosidase inhibitory, and antimicrobial activities. Lupane carboxamides, conjugates with diaminopropane, triethylenetetramine, and branched C3-cyanoethylated polyamine methyl betulonate showed high cytotoxic activity against most of the tested cancer cell lines with GI50 that ranged from 1.09 to 54.40 µM. Betulonic acid C28-conjugate with triethylenetetramine and C3,C28-bis-aminopropoxy-betulin were found to be potent micromolar inhibitors of yeast α-glucosidase and to simultaneously inhibit the endosomal reticulum α-glucosidase, rendering them as potentially capable to suppress tumor invasiveness and neovascularization, in addition to the direct cytotoxicity. Plausible mechanisms of cytotoxic action and underlying disrupted molecular pathways were elucidated with CellMinner pattern analysis and Gene Ontology enrichment analysis, according to which the lead compounds exert multi-target antiproliferative activity associated with oxidative stress induction and chromatin structure alteration. The betulonic acid diethylentriamine conjugate showed partial activity against methicillin-resistant S. aureus and the fungi C. neoformans. These results show that triterpenic polyamines, being analogs of steroidal squalamine and trodusquemine, are important substances for the search of new drugs with anticancer, antidiabetic, and antimicrobial activities.